Paralysis at the Adolescent Gate: Peter Pan Meets Godzilla. (2nd January 2016) - Levy-Warren, Marsha
ABSTRACT: When a 13-year-old develops a disturbance so great that he is unable to go to school, is disinclined to see his friends or go out, and is deeply sad and anxious, clinicians tend to turn to his history to understand what is happening. In the case of Peter, what emerges is that it is not his history but rather what he perceived to be his future that led to his breakdown. This article explicates how the perception of what was to come dovetailed with where he was in his development, and how these coalesced to create an emotional paralysis.